(untitled) (Journal of the College of Basic Education, 2022)
In this work some metal samples made from pure copper and Brass alloy were prepared and machined as a half bushes with a diameter of 1.6 cm and length of 1.5 cm .Rockwell method was used to measured the hardness of samples before running . These samples were placed in wear system testing under lubricated condition (Iraqi Oil).Different normal loads were applied to copper and brass samples at different sliding time ,weight loss was measured for all sample by weighed the sample before and after running and the difference between them represent the weight loss. Different figures were ploted between weight loss and wear parameters.